Incidence of low birth weight and associated risk factors during March 2002-2003 in Tonekabon, Iran - S.Z. Hosseini; M.H. Bahadori; H. Fallah Bagher Shaidaei (Journal of Mazandaran University of Medical Sciences, 2005)
Background and purpose: Low birth weight (LBW; birthweight 2500 g. or below) is a public health problem, because it is associated with increased risk of morbidity and mortality. This prospective study was conducted during March 2002 - 2003, to determine the incidence of low birth weight infants and associated risk factors in neonates born at Shahid Rajaee Hospital in Tonekabone, Iran.Materials and methods: For every LBW case, maternal age, sex, gestational age, parity, route of delivery and spacing between pregnancies of low birth weight were analyzed. For control, the first baby born before and immediately after the LBW baby who weighed more than 2500 g. at birth were analyzed.Results: The results revealed that the incidence of low birth weight was 4.2 % which is lower than population of other cities and only 0.34% (7 cases) of newborns weighted 1500 g. or less. The higher incidence of low birth weight was found in the primigravid (P=0.042), in cesarean section (P=0.025) and close spacing of pregnancy (P=0.033). Maternal age and sex of baby had no significant effect on the incidence of low birth weight. There were more premature deliveries in cases than controls (P=0.000).Conclusion: According to present findings, LBW incidence of albeit in Tonekabon in comparison with other cities throught the country is at acceptable level, prevention of premature delivery and conduction of health education programs for high risk groups, especially primigravid can lower the rates.